2008
DOI: 10.1097/shk.0b013e318164f013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Hepatic Injury After Trauma-Hemorrhage via Estrogen Receptor-Related Pathway

Abstract: Resveratrol administration after adverse circulatory conditions is known to be protective, however, the mechanism by which resveratrol produces the salutary effects remains unknown. Recently, it was shown that resveratrol activates estrogen receptor (ER) in endothelial cells. We hypothesized that resveratrol administration in males after trauma-hemorrhage decreases cytokine production and protects against hepatic injury through an ER-dependent pathway. To study this, male Sprague-Dawley rats were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…Resveratrol has been shown to have cardioprotective effects during ischemia reperfusion [10], and our studies have shown that resveratrol can attenuate hepatic injury after trauma-hemorrhage [9]. The PI3K/Akt pathway is known to be an endogenous negative feedback or compensatory mechanism, which serves to limit proinflammatory and chemotactic events in response to injury [11][12][13].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Resveratrol has been shown to have cardioprotective effects during ischemia reperfusion [10], and our studies have shown that resveratrol can attenuate hepatic injury after trauma-hemorrhage [9]. The PI3K/Akt pathway is known to be an endogenous negative feedback or compensatory mechanism, which serves to limit proinflammatory and chemotactic events in response to injury [11][12][13].…”
Section: Introductionmentioning
confidence: 92%
“…The time required for maximum hemorrhage was about 45 min, the volume of maximum hemorrhage was about 60% of the calculated circulating blood volume, and the total hemorrhage time was about 90 min [20]. Thirty minutes before the end of the resuscitation period, the rats received resveratrol (30 mg/kg, intravenously) [9], resveratrol plus the PI3K inhibitor wortmannin (1 mg/kg, intravenously at the beginning of resuscitation), wortmannin or an equal volume of the vehicle (w0.2 mL, 10% DMSO; Sigma, St. Louis, MO, USA) [8]. The catheters were then removed, the vessels ligated, and the skin incisions closed with sutures.…”
Section: Rat Trauma-hemorrhage and Resuscitation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, because the α subtype is widely expressed, many of the anti-obesity effects of these compounds may be due to estrogen receptor-independent signaling. Interestingly though, a recent study demonstrated an estrogen receptor-dependent effect of resveratrol to reduce hepatic IL-6 in a trauma-hemorrhage model (Yu et al, 2008). Additionally, both genistein and daidzein have also been shown to prevent endoplasmic reticulum stress activation in neuroblastoma cells .…”
Section: Anti-inflammatory and Anti-obesity Activity Of Phytoestrogensmentioning
confidence: 98%